(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Preschool education is the foundational stage in a child’s personal development. In recent years, extensive reforms have been carried out in preschool education systems around the world, including in Latin American countries, to improve quality and accessibility. This article analyzes the preschool education system in Latin American countries, its theoretical foundations, and practical experiences.